272 PHYSIOTHERAPISTS' EXPERIENCES OF WORKING IN RESIDENTIAL CARE IN THE REPUBLIC OF IRELAND DURING COVID-19. (25th October 2022) - O'Callaghan, S; Reilly, A; O'Shea, O
Abstract: Background: COVID-19 was officially declared a pandemic in March 2020. Social distancing and visiting restrictions were introduced in Irish residential care units in March 2020. The impact of COVID-19 and associated restrictions on physiotherapists working in residential care in the Republic of Ireland (ROI) is unknown. This study aimed to explore the experience of physiotherapists working in residential care units in the ROI during the COVID-19 pandemic. Methods: A qualitative phenomenological study design was used. Physiotherapists working in residential care units were invited to participate in one-to-one semi-structured interviews from December 2021 to March 2022. Participants were recruited via purposive and snowball sampling. Data were analysed using reflexive thematic analysis by two independent reviewers. Results: Seven one-to-one semi-structured interviews were conducted among five female and two male physiotherapists. Four major themes emerged: (i) service adaptation (ii) communication (iii) physical and emotional impact of COVID-19 pandemic on staff and (iv) physical and emotional impact of COVID-19 pandemic on residents. A number of subthemes were identified under each theme. Participants experienced changes in service delivery including redeployment, reduced resident contact and social distancing. These changes resulted in innovation, mainly through telehealth. Participants felt communication from managers could be improved through clarity regarding protocol changes. The pandemic stimulated enhanced inter-professional communication among physiotherapists. Some participants contracted COVID-19 resulting in residual physical impairments. Participants were affected emotionally through the increased stress experienced due to COVID-19 restrictions. Residents experienced isolation due to visiting restrictions. Due to reduced physiotherapy input participants observed reduced physical functioning among residents. Conclusion: COVID-19 and its associated restrictions had a profound impact on physiotherapists working in residential care units as well as on residents. The extent of this impact is only beginning to emerge. Planning for future pandemics should consider the long-term physical and emotional consequences of restrictions on both physiotherapists and residents.